Effect of Ni-Mn ratio on structural, martensitic and magnetic properties of Ni-Mn-Co-Ti ferromagnetic shape memory alloys. (18th July 2018) - Hassan, Najam ul; Shah, Ishfaq Ahmad; Jelani, Mohsan; Naeem, M; Riaz, Saira; Naseem, Shahzad; Xu, Feng; Ullah, Zaka
Abstract: In this work, we study the structural, martensitic and magnetic characteristics of all- d -metal Ni35− x Mn35+ x Co15 Ti15 ( x = 0, 1, 2, 3) alloys. The x-ray diffraction analysis confirms that the alloy system crystallizes as 5 M modulated and L 10 non-modulated martensite with a small fraction of B 2 austenite phase for x = 0. The proportion of austenite phase increases while the martensite phase decreases with increase in x, and B 2 austenite phase becomes dominant for x = 3. Large endothermic/exothermic peaks with distinct thermal hysteresis in differential scanning calorimetry analysis indicate the martensitic/reverse martensitic transformations. The martensitic transformation temperature decreases considerably with increase in x . Thermal magnetization ( M-T ) curves show an abrupt variation in magnetization from weak magnetic martensite to ferromagnetic austenite near martensitic transformation temperature. M ( H ) loops measured at room temperature confirm the ferromagnetic behaviour of all the prepared samples. Isothermal magnetization ( M-H ) curves of Ni34 Mn36 Co15 Ti15 at various temperatures show that the magnetic field can induce the magnetostructural transformation in this alloy. A magnetic entropy change of 11.3 J K −1 kg −1 is observed at room temperature (290 K) in Ni34 Mn36 Co15 Ti15 alloy.